Usefulness of Electrocardiographic QRS/T angles With versus Without Bundle Branch Blocks to Predict Heart Failure (From the Atherosclerosis Risk in Communities [ARIC] Study) - Zhang, Zhu-ming (2014)
Repolarization abnormalities in the setting of bundle branch blocks (BBB) are generally ignored. We used Cox regression models to determine hazard ratios (HR) with 95% confidence intervals (CI) for incident heart failure (HF) associated with wide spatial and frontal QRS/T angle (upper 25(th) percentile of each) in men and women with and without BBB. This analysis included 14,478 participants (54.6% women, 26.4% blacks, 377 (2.6%) with BBB) from the Atherosclerosis Risk in Communities Study who were free of HF at baseline. Using No-BBB with normal spatial QRS/T angle as the reference group, the risk for HF in multivariable adjusted models was increased 51% for No-BBB with wide spatial QRS/T angle (HR 1.51, CI 1.37–1.66), 48% for BBB with normal spatial QRS/T angle (HR 1.48, CI 1.17–1.88), and the risk for incident HF was increased over 3-fold for BBB with wide spatial QRS/T angle (HR 3.37, CI 2.47–4.60). The results were consistent across subgroups by sex. Similar results were observed for the frontal plane QRS/T angle. In the pooled BBB group excluding RBBB, a positive T wave in lead aVR and heart rate 70 bpm and higher were also potent predictors of incident HF similar to the QRS/T angles. In conclusion, both BBB and wide QRS/T angles are predictive of heart failure, and concomitant presence of both carries a much higher risk than for either predictor alone. These findings suggest that repolarization abnormalities in the setting of BBB should not be considered benign or an expected consequence of BBB.